Big Data In E-Governance Management - Saluja, Harshita; Asthana, Pallavi; Mishra, Sumita; Kumar, Sachin; Hazela, Bramah (International Journal of Computer Sciences and Engineering, 2018)
Large amount of data produced through humans, machines and automated system can be monitored for improving the efficiency of systems. This data can be real time monitored through Big Data analysis. Big Data could be structured, unstructured or semi-structured and is characterized by Volume, Velocity, Variety, Veracity and Value. The data is novel, dynamic, and scalable. Data analysis performed on Big Data can be highly useful in E-governance. This paper explores the five ways in which big data is characterized, methods of its classification, Big data management and its role in effective implementation of e-governance like education, health care, revenue etc., where huge amount of data is generated. This data is useful in understanding the factors that can be monitored and analyzed for improvement and betterment of current policies initiated by government.